Short- and long-term scaling behavior of blood pressure and pulse arrival time during sleep in healthy controls and patients with obstructive sleep apnea - Karsten Berg; Jan W. Kantelhardt; Martin Glos; Thomas Penzel; Niels Wessel; Ronny P. Bartsch (PLoS ONE, 2026)
Obstructive sleep apnea (OSA) is characterized by recurrent respiratory events that trigger autonomic arousals and blood pressure (BP) surges, contributing to elevated cardiovascular risk. Photoplethysmography (PPG)-derived timing markers such as pulse arrival time (PAT) are frequently used as noninvasive surrogates of BP dynamics, yet their interpretation is confounded by the pre-ejection period and peripheral vascular effects. Here, we used detrended fluctuation analysis (DFA) to quantify short- and long-term scaling exponents of continuous blood pressure (Portapres), PPG-, and PAT-derived signals across sleep stages in healthy individuals and patients with OSA. Directly measured systolic and diastolic BP exhibited a robust short- to long-term crossover across all sleep stages, with elevated short-range exponents ( α 1 > 1 ) and lower long-range exponents ( α 2 < 1 ), reflecting well-organized autonomic and vascular control. In OSA, this crossover persisted but was visibly attenuated, consistent with reduced short-term adaptability of cardiovascular regulation. In contrast, PAT-based indices showed substantially weaker short-range correlations and minimal crossover structure. Systolic PAT displayed almost no separation between α 1 and α 2 , and PPG-derived measures exhibited scaling patterns that differed fundamentally from BP. Across modalities, PAT (whether derived from BP or PPG) failed to reproduce the multiscale organization characteristic of beat-to-beat BP dynamics. Group comparisons further identified systolic BP scaling, particularly the short-range exponent α 1 , as the most sensitive marker of cardiovascular dysregulation in OSA, whereas PAT and PPG provided complementary but physiologically distinct information related to peripheral vascular and autonomic modulation. These findings demonstrate that PAT and PPG timing measures should not be used as surrogates for BP in fractal or scaling analyses and underscore the unique diagnostic value of BP-derived scaling behavior for assessing cardiovascular regulation during sleep.